DINAMIKA KELOMPOK TANI DAN PEMBANGUNAN HUTAN RAKYAT DI KABUPATEN SERANG PROVINSI BANTEN - indah bangsawan; Hardjanto Hardjanto; Yulius Hero (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2016)
The success of  the development of  Private Forest (PF) can not be separated from the farmer groups (FG). The research aimed to: (1) analyzing the organization and rules of  FG and (2) analyzing the relationship between development of  FG and its PF that managed by this FG. First analysis by using historical case studies or organization method while second analysis by using ethnographic method. The results showed that the organizational structure of  FG which was formed since the beginning or as a result of  reform was simple so it would be ease to facilitate on the decision making. Norms of  the group was as the result of  the deliberation agreed upon, understood and adhered to by all members, even though it was not formally written. The norm of  the board executives and members were not been stated formally but it was reported during group deliberation and so that it running well. FG consisting of  15 people and was formed in 2002 and amended in 2011 and it growing continuously until 2014. The development of  the FG was characterized by growing type of  business, assets of  the FG and the land area of  PF was managed by FG.